Uso de software de comparação 3D em projetos de estruturas metálicas - Franceschetto, Wellington (2024)
With technological advances in the area of ​​industrial projects, the use of software comparison can contribute to reducing errors. The central problem addressed in the present work, cites the high incidence of failures and inconsistency in structural designs metals, which consequently result in increased costs and schedules. A introduction of 3D and 2D comparison software is explored as a potential solution to minimize these problems. The literature used to develop the research are based on concepts and project management, development of product and metallic structures. The case study was adopted as a procedure methodological, where the proposed objectives were to reduce errors with the use of software and its pros and cons. Finally, it was found that the software minimizes errors, reducing rework costs, giving more agility in the final project conference, however, it still has a high acquisition cost.